Corporate carbon reporting: Improving transparency and accountability - Stephen Comello; Julia Reichelstein; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Numerous multinational firms have recently pledged to reduce their greenhouse gas emissions to a net-zero position by the year 2050. These pledges currently lack a unified measurement and reporting structure, leaving the public unsure about the extent of the corporate commitments. Here, we propose a Time-Consistent Corporate Carbon Reporting (TCCR) standard that entails an initial forecast of a firm's future carbon emissions trajectory, periodic revisions of the earlier forecasts, and updates on emissions reductions actually achieved at different points in time. The TCCR standard is applicable to alternative carbon footprint metrics, including a company's direct emissions, carbon emissions in goods sold, or the carbon footprint assessed for individual sales products. Companies adopting the TCCR standard will provide added transparency and accountability for their carbon disclosures.
Keywords: M41; Q53; Q54; 330; Carbon emissions; Net-zero pledges; Accountability